ESR1-Mediated Regulation of Slc2a4 Gene Expression by Estrogen: Demonstration of a Potential Estrogen Responsive Element (ERE) in the Slc2a4 Gene Promoter - Laurindo, Caroline Pancera; Gregorio, Karen Cristina Rego; de Freitas, Helayne Soares; Bezerra, Camila Nogueira Alves; Okamoto, Maristela Mitiko; Seraphim, Patricia Monteiro; Festuccia, William Tadeu; Machado, Ubiratan Fabres (British Journal of Healthcare and Medical Research, 2026)
This study investigated the transcriptional activity (gene reporter assay) of some putative estrogen responsive elements (EREs) in the Slc2a4 gene promoter region, which could contribute to understanding the estrogen receptor 1 (ESR1) mediated enhancer role of estradiol (E2). In 3T3L1 adipocytes, E2 and ESR1-selective agonist (PPT) increased (by 35%, p<0.01) the expression of Slc2a4 mRNA; ESR1-selective antagonist (MPP) abrogated the E2 effect. In transiently transfected HEK293-FT cells, the basal Slc2a4-Luciferase activity of 5’-500, 5’-250 and 5’-149 bp segments of the promoter revealed that the loss of the -500/-250 bp segment reduces the unstimulated Slc2a4-Luc activity (60%, p<0.001), a response attributed to the loss of seven known binding-sites of enhancer transcription factors. Besides, E2/PPT increased (~150%, p<0.001) the relative Slc2a4-Luc activity of all constructs, revealing that the ESR1-mediated E2-induced transcriptional activity is preserved in all constructs, and that the putative ERE half-sites, encompassed in -250/-149 bp segment, do not display transcriptional activity. Finally, 5’-500 bp and 5’-149 bp constructs, containing four mutated nucleotides in the putative complete Slc2a4 ERE, lost their responsiveness to E2. In conclusion, this study reveals an imperfect complete Slc2a4 ERE site (-59/-46 bp), which is involved in the ESR1-mediated E2-induced enhancing of the Slc2a4 gene expression.